Development Crisis in the Philippines - Magno, Francisco A. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Two years after the February 1986 Uprising which toppled the Marcos regime, the Philippine economy under the Aquino government continues to suffer from the same development crisis which afflicted the previous regime. This stems from the fact that the Aquino government has chosen to adopt the same economic model for development followed by the Marcos regime. Such an economic model subsists on the belief that heavy reliance on foreign investments and exports markets would spur economic growth, and thus engender development in the periphery. This calls for no less than the maintenance of the peripheral economy's integration within the global capitalist economy. The pursuit of a dependent form of capitalist development under the authoritarian regime of Marcos led not to the development of the economy, but to the development of a crisis. It is doubtful therefore to assume now that the liberal democratic regime of Aquino would be capable of taking the economy on the road to recovery by using the same development path used by the Marcos regime in plunging the country into crisis.